2013
DOI: 10.1111/head.12233
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Wisely in Headache Medicine: The American Headache Society's List of Five Things Physicians and Patients Should Question

Abstract: In an effort to draw attention to tests and procedures associated with low-value care in headache medicine, the American Headache Society (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 22 publications
2
108
2
4
Order By: Relevance
“…The diagnosis and pathophysiologic mechanism of pain have implications for symptomatic pain treatment with medication. For example, evidence is limited or insufficient for improved pain or function with long-term use of opioids for several chronic pain conditions for which opioids are commonly prescribed, such as low back pain (182), headache (183), and fibromyalgia (184). Although NSAIDs can be used for exacerbations of nociceptive pain, other medications (e.g., tricyclics, selected anticonvulsants, or transdermal lidocaine) generally are recommended for neuropathic pain.…”
Section: Evidence Typementioning
confidence: 99%
“…The diagnosis and pathophysiologic mechanism of pain have implications for symptomatic pain treatment with medication. For example, evidence is limited or insufficient for improved pain or function with long-term use of opioids for several chronic pain conditions for which opioids are commonly prescribed, such as low back pain (182), headache (183), and fibromyalgia (184). Although NSAIDs can be used for exacerbations of nociceptive pain, other medications (e.g., tricyclics, selected anticonvulsants, or transdermal lidocaine) generally are recommended for neuropathic pain.…”
Section: Evidence Typementioning
confidence: 99%
“…Recently, Choosing Wisely guidelines have focused on overuse by questioning the use of diagnostic neuroimaging in 2 highly prevalent neurologic conditions: headache and peripheral neuropathy. 2,3 Guideline discordant neuroimaging overuse appears to be common for headache 4,5 and peripheral neuropathy. [6][7][8] At the same time, underuse of neuroimaging in some highrisk headache patients 9 and diagnostic laboratory testing 10 in neuropathy patients likely exists.…”
mentioning
confidence: 99%
“…This was contrary to the guidelines originally laid down by Frishberg, [2] and later confirmed in a number of studies. [3,4] These guidelines suggested that for migraines, there was no difference in the incidence of clinically meaningful pathology to the incidence in the general population, and that neuroimaging is unnecessary. [5] Exceptions to these recommendations are the presence of the following red flags:…”
Section: Neuroimaging In Migrainementioning
confidence: 99%